Social entrepreneurship in the Czech Republic: Current trends in research on hybridity - Vaceková, Gabriela; Soukopová, Jana; Křenková, Tereza (Univerzita Pardubice, 2015)
The hybridity phenomenon has received increasing attention in the scientific literature worldwide. However, this is largely western literature, which is not perfectly suited to the transitional context of Central and Eastern Europe, respecting its specific features. The lack of relevant research on hybridity in the post-communist countries shows a considerable research gap that strongly indicates the need for deeper insight. The paper contributes to the conversation by rethinking hybridity in the context of transitional economies. The typical hybrid organizations, combining a market orientation with a social mission, are social enterprises. The discourse on social enterprise is quite different across countries, including across (post-) transitional economies. The Czech Republic is a CEE country still lacking legislative regulation on social entrepreneurship. The paper provides a comprehensive picture of the driving forces, challenges, and opportunities for social entrepreneurship in the specific historical, socio-economic, legislative, and political conditions of the Czech Republic. The main results presented in the paper show key historical events explicitly influencing social entrepreneurship and its current state based on up-to-date data, enabling the assessment of current trends in research on hybridity in the Czech Republic.
Keywords: hybrid organizations; social economy; social entrepreneurship; Czech Republic; H44; L31; L33